Islamic Financial Literascy For Members Majelis Ta’lim Raudatul Jannah in Tulehu Village - Fatmah Watty Pelupessy (MANGENTE: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
Abstract: This comminity service activity (PkM) aims to provide understanding to members of the Majelis Ta’lim Raudatu Jannah about islamic finance as well as contracts and products in islamic banking located in Tulehu village. This activity is carried out by providing socialization regarding islamic financial institutions (especially isslamic banking). The socialization activity was followed by sharing and discussion activities regarding the material that had been delivered. Keywords: Literacy, Islamic FinanceAbstrak: Kegiatan pengabdian kepada masyarakat (PkM) ini bertujuan untuk memberikan pemahaman kepada anggota majelis ta’lim raudatul jannah tentang keuangan syariah serta akad dan produk-produk dalam perbankan syariah.kegiatan ini melibatkan seluruh anggota Majelis Ta’lim Raudatul Jannah yang berlokasi di Desa Tulehu. Kegiatan ini dilaksanakan dengan memberikan  sosialisasi mengenai lembaga keuangan syariah (khususnya perbankan syariah). Kegiatan sosialisasi dilanjutkan dengan kegiatan sharing dan diskusi mengenai materi yang telah disampaikan. Kata kunci: Literasi, Keuangan Syariah